Evolutionary programming based technique for optimal capacitor sizing in distribution system for loss minimization / Mohd Hafiz Jusoh - Jusoh, Mohd Hafiz (2007)
Power losses in distribution system have become the most concerned issue in power losses analysis in most power system study. In effort of reducing power losses within distribution system, real power compensation has become increasingly important as it affects the operational, economical and quality services for electric power systems. This project report presents Evolutionary Programming Based Technique for Optimal Capacitor Sizing in Distribution System for loss minimization. The objective is to minimize the distribution loss in power system. The study involved the development of EP engine to minimize distribution loss using capacitor placement technique. A 69-distribution system is used to implement the proposed EP technique. Results from the study revealed that the proposed optimal capacitor placement technique has significantly minimized distribution loss. Minor modification in the developed engine could be performed to solve other optimization problems.